Determination of Hb Levels in Adolescent Girls in Depok City: The Role of Sociodemographics, Attitudes, and Knowledge of Iron Tablets - Nurmadinisia, Rahmi; Susilawati, Susilawati; Farna, Ritta (Al GIZZAI: PUBLIC HEALTH NUTRITION JOURNAL, 2026)
Introduction: Anemia in adolescent girls leads to decreased academic achievement, productivity, and quality of life. Low adherence to Iron Supplement Tablet (IST) consumption, low dietary iron intake, and parental sociodemographic factors are the main risk factors for anemia. This study aims to analyze the relationship between parental sociodemographic factors, attitudes, and knowledge about IST and hemoglobin (Hb) levels among students at SMA IT Raflesia, Depok City. Methods: This analytical observational study with a cross-sectional approach was conducted in September 2025 at SMAIT Raflesia, Depok City. A sample of 70 adolescent girls was selected using purposive sampling. Primary data were collected through questionnaires and Hb level examinations. Data analysis using SPSS included univariate analysis, bivariate analysis (Pearson correlation), and multivariate analysis (multiple linear regression). Results: The mean Hb level of the respondents was 11.89 g/dL. Correlation tests showed a significant relationship between the Hb levels of adolescent girls and parental education (p=0.001), adolescent attitude (p=0.001), and knowledge about TTD (p=0.026). Conversely, there was no significant relationship between parental occupation and respondents' Hb levels. Conclusion: Parental education, adolescent attitudes, and knowledge about Iron Supplement Tablets (IST) are variables that show a significant association with hemoglobin levels in adolescent girls, while parental occupation does not show any relationship. Strengthening education about IST and increasing family support are necessary to optimize hemoglobin levels in adolescents.